Clinical characterisation of sensory neuropathy with anti-FGFR3 autoantibodies. Issue 1 (5th November 2019) - Tholance, Yannick; Moritz, Christian Peter; Rosier, Carole; Ferraud, Karine; Lassablière, François; Reynaud-Federspiel, Evelyne; França Jr, Marcondes C; Martinez, Alberto R M; Camdessanché, Jean-Philippe; Antoine, Jean-Christophe
Abstract : Objective: Sensory neuropathies (SNs) are often classified as idiopathic even if immunological mechanisms can be suspected. Antibodies against the intracellular domain of the fibroblast growth factor receptor 3 (FGFR3) possibly identify a subgroup of SN affecting mostly the dorsal root ganglion (DRG). The aim of this study was to identify the frequency of anti-FGFR3 antibodies and the associated clinical pattern in a large cohort of patients with SN. Methods: A prospective, multicentric, European and Brazilian study included adults with pure SN. Serum anti-FGRF3 antibodies were analysed by ELISA. Detailed clinical and paraclinical data were collected for each anti-FGFR3-positive patient and as control for anti-FGFR3-negative patients from the same centres ('center-matched'). Results: Sixty-five patients out of 426 (15%) had anti-FGFR3 antibodies, which were the only identified autoimmune markers in 43 patients (66%). The neuropathy was non-length dependent in 89% and classified as sensory neuronopathy in 64%, non-length-dependent small fibre neuropathy in 17% and other neuropathy in 19%. Specific clinical features occurred after 5–6 years of evolution including frequent paresthesia, predominant clinical and electrophysiological involvement of the lower limbs, and a less frequent mixed large and small fibre involvement. Brazilians had a higher frequency of anti-FGFR3 antibodies than Europeans (36% vs 13%, p<0.001), and a more frequent asymmetrical distribution of symptoms (OR 169, 95% CI 3.4 to 8424). Conclusions: Anti-FGFR3 antibodies occur in a subgroup of SN probably predominantly affecting the DRG. Differences between Europeans and Brazilians could suggest involvement of genetic or environmental factors.